Seminal characterization of some elite Ethiopian indigenous breeds of bull - SORI, HUNDERRA; PRASAD, SHIV; ZEWDIE, EMIRU (The Indian Journal of Animal Reproduction, 2023)
The semen of six indigenous bulls consisting of Barca, Boran, Horro and Sheko breeds maintained at National ArtificialInsemination Center (NAIC), Kaliti, Addis Ababa, (Ethiopia) were evaluated for physico-morphological parameters, biochemicalparameters (GOT, GPT, ACP, ALP, total protein) and hormonal assay (testosterone). Semen was collected forthirteen weeks, once a week by using artificial vagina. The overall mean (SE) value for the semen characteristics studied werevolume 4.84 (0.20) ruJ, mass motility 3.15 (0.11 ), individual motility 68.72 (1.37) %, concentration 1.54 (0.07) billions/ml,total count 7.35 (0.4 7) billions/ejaculate, viable number 5.10 (0.33) billions/ejaculate, total morphologically normal number7.12 (0.45) billions/ejaculate, live percentage 79. 73 (0.65), percent morphologic normal 94.70 (0.38), per cent normal acrosome96.99 (0.60), GOT I 530.91 (60. I 5) u/1, GPT 131.99 (9.36) U/L, ALP 3333.98 (608.84) U/L, ACP 8003.68 (716.06) U/L, totalprotein 7.38 (0.26) gm/di, testosterone 2.84 (0.3) ng /ml. It could be concluded that seminal attributes were comparable tonormal fertile bulls of other breeds based on the evaluation of fresh semen parameters.
Keywords: Ethiopia; NAIC; indigenous breeds physico-morphological; biochemical parameters; semen; Spermatozoa